Effect Of Price And Food’s Quality On Consumer Buying Interest Mediated By Brand Image In Culinary Tourism Kebon Ayu Village, West Lombok Regency - Baiq Firli Amanda Sari; Sapto Supriyanto; Andhi Supriyadi (International Conference On Digital Advanced Tourism Management And Technology, 2023)
The aim of this research is to examine and elucidate the relationship between food quality and price and customer buying interest in culinary tourism in Kebon Ayu village, West Lombok Regency, as it is mediated by brand image. The focus of this extensive study is on the statistical processing of numerical data, specifically looking at the factors that arise. The study's findings will explain how food prices and quality affect consumer purchasing interest in culinary tourism in Kebon Ayu village, West Lombok Regency, and how this is mediated by brand image.. The sample of this study was tourists who came to visit the culinary tourism of Kebon Ayu village as many as 120 people. Data collection techniques using questionnaires and data were tested and analyzed using multiple linear regression with SPSS Version 20. Based on the results of research data analysis, it can be concluded that (1) price affects buying interest (2) food quality affects buying interest (3) brand image affects buying interest (6) price affects buying interest mediated by brand image (7) food quality affects buying interest mediated by brand image.